2019
DOI: 10.26814/cps2020006
|View full text |Cite
|
Sign up to set email alerts
|

Cause and effect relationships, multivariate approach for inoculation of Azospirillum brasilense in corn

Abstract: Beneficial bacteria to corn crop, such as Azospirillum brasilense, can bring consistent gains for the farmer. In this sense, the objective of this work was to evaluate the cause and effect relationships and multivariate approach of Azospirillum brasilense inoculation in corn genotypes. The study was conducted in the municipality of Mineiros-GO, Brazil. The experimental design was a randomized block in 12x2 factorial, corresponding to twelve corn hybrids (20A78,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Regarding SD, AG 9000 showed the higher average only in the first off-season, and not in the second one, whereas among other hybrids there were no differences. Ferreira et al (2020) found no differences in SD between the selected hybrids whether A. brasilense was present or not. Moreover, this parameter did not seem to be influenced by soil cultivation practices or inoculation since it was found no pattern to explain the stem diameter of the hybrids.…”
Section: Effect Of Inoculation On Morphophysiological Traitsmentioning
confidence: 66%
See 3 more Smart Citations
“…Regarding SD, AG 9000 showed the higher average only in the first off-season, and not in the second one, whereas among other hybrids there were no differences. Ferreira et al (2020) found no differences in SD between the selected hybrids whether A. brasilense was present or not. Moreover, this parameter did not seem to be influenced by soil cultivation practices or inoculation since it was found no pattern to explain the stem diameter of the hybrids.…”
Section: Effect Of Inoculation On Morphophysiological Traitsmentioning
confidence: 66%
“…Regarding yield parameters, Ferreira et al (2020) observed enhanced productivity of DKB 310 regardless Average followed by the same capital letter in the column (Genotypes) and lowercase letter in the line (NT and FS) do not differ significantly by the Tukey test (P>0.05). (n=5).…”
Section: Effect Of a Brasilense On Corn Yieldmentioning
confidence: 88%
See 2 more Smart Citations
“…In the same year, both single and intercropped corn, inoculated in both soils, showed higher grain yields of 5,171 and 5,744 kg ha -1 , respectively, than the corn that did not receive any inoculation (Table 2). Lana et al (2012) reported that inoculation with Azospirillum provided increases of up to 14.0% in corn grain yield, even without the addition of N. Plant growthpromoting bacteria, such as A. brasilense, can lead to consistent gains without the need for large investments in N fertilizers (Ferreira et al, 2020).…”
Section: Resultsmentioning
confidence: 99%